2008
DOI: 10.4238/vol7-2gmr443
|View full text |Cite
|
Sign up to set email alerts
|

Initial stage of development and migratory behavior of Toxocara canis larvae in BALB/c mouse experimental model

Abstract: ABSTRACT. In the present study, the initial developmental stage of Toxocara canis eggs and larvae, and number of recovered larvae from BALB/c mouse-infected organs are described. In vitro culture of T. canis detects the frequencies of interphasic, mitotic and embryonated eggs only within a 7-day period. Analysis by egg counting was carried out for 32 days. The results showed that at 7 days after cultivation, the frequency of larvae was 50.4% and that this frequency reached 52.8% in 32 days. In the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…It has been observed that larvae can invade the mouse CNS during the initial phase of infection; with cumulative infection doses and progress of infection, the probability of additional organ involvement increases (Sprent 1955;Dunsmore et al 1983;Good et al 2001;Hamilton et al 2006;Camparoto et al 2008). Neurotoxocarosis can be manifested by behavioral changes: the experimentally infected mice were less aggressive, less explorative, and showed some impairment in learning and memory (Cox and Holland 1998;Cox and Holland 2001a, b;Hamilton et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…It has been observed that larvae can invade the mouse CNS during the initial phase of infection; with cumulative infection doses and progress of infection, the probability of additional organ involvement increases (Sprent 1955;Dunsmore et al 1983;Good et al 2001;Hamilton et al 2006;Camparoto et al 2008). Neurotoxocarosis can be manifested by behavioral changes: the experimentally infected mice were less aggressive, less explorative, and showed some impairment in learning and memory (Cox and Holland 1998;Cox and Holland 2001a, b;Hamilton et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…This rodent may also be infected with other helminthic and protozoan parasites facilitating the study of concomitant infections 6,20 .…”
Section: Introductionmentioning
confidence: 99%
“…La afectación del sistema nervioso central (SNC) es inusual 2,7,8 y comprende la meningitis 2,8,9 , encefalitis 8,10 , mielitis 2,7,9,10-13 , o radiculitis 8 . Sin embargo, en modelos animales, larva migrans migra con frecuencia al SNC 14 .…”
Section: Discussionunclassified